Effects of Previous Overt Hyperthyroidism due to Graves’ Disease on Bone Mineral Density (BMD) in Euthyroid Pre and Post Menopausal Females - Muhammad Adnan Saeed, Riaz Ahmad Kirn-e, Muneera Rabbani (Journal of Rawalpindi Medical College, 2015)
Background: To determine the effects of previous overt hyperthyroidism due to Graves’ disease on BMD in euthyroid pre and post menopausal females. Methods: In this cross-sectional, non-interventional study,fifty patients with previous hyperthyroidism due to Graves’ disease (premenopausal:25, postmenopausal: 25) who remained euthyroid for at least 6 months prior to study were included and compared with fifty- matched respective controls. Free thyroxine (FT4), TSH, and BMD were measured. Comparison was made between two groups and also between patients and controls in each group. Results: Statistically significant (p <.0.05) lower whole body BMD expressed as Z-score was observed in post-menopausal women having history of hyperthyroidism due to Graves’ disease than matched controls. Bone mineral density, expressed as Z-score in whole body and lumbar spine was significantly lower in group II (post-menopause) in comparison to group I (pre-menopause) patients. Time of euthyroidism and time of evolution of disease has significant effect on BMD in post-menopausal women. Conclusion: Graves’ hyperthyroidism affects BMD only in post menopausal females even after achievement of euthyroid status.